2013
DOI: 10.1590/s0102-05362013000100015
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry yield efficiency and its correlation with temperature and solar radiation

Abstract: The impact that future climatic conditions will have on agricultural productivity depends on the sensitivity to each environmental factor and relative changes in temperature, precipitation and UV-B radiation. The strawberry (Fragaria x ananassa) is a microclimatic crop cultivated almost worldwide and Spain is the world's second-largest strawberry producer after the USA. Strawberry production in Huelva has been affected by climate change in recent decades. Temperature and solar radiation are primary environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 22 publications
2
31
0
5
Order By: Relevance
“…Strawberry yield and quality can be affected by day length, temperature, soil characteristics, altitude, latitude, cultivation system and management practices (Kruger et al, 2004) and the variation in strawberry yield among four states can be attributed to these factors. One of the most important factors was the climate (Palencia et al, 2013) which was totally different among these four states. California's unique climate (moderate temperature year round) is a perfect condition for growing strawberry which result in high yield (1.25 million tons strawberry production in 2014 (90% of the U.S. strawberry production) (USDA, 2015)).…”
Section: Resultsmentioning
confidence: 99%
“…Strawberry yield and quality can be affected by day length, temperature, soil characteristics, altitude, latitude, cultivation system and management practices (Kruger et al, 2004) and the variation in strawberry yield among four states can be attributed to these factors. One of the most important factors was the climate (Palencia et al, 2013) which was totally different among these four states. California's unique climate (moderate temperature year round) is a perfect condition for growing strawberry which result in high yield (1.25 million tons strawberry production in 2014 (90% of the U.S. strawberry production) (USDA, 2015)).…”
Section: Resultsmentioning
confidence: 99%
“…Weather influence on strawberry has been documented in various studies. For instance, [3] examined strawberry yield efficiency and its correlation with temperature and solar radiation and found strawberry yield was significantly correlated with solar radiation. There are various other studies that showed the importance of solar radiation in strawberry growth and development overall [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…; Palencia et al. ). The characteristics of railways therefore have the potential to accelerate maturation and increase the abundance of berry‐producing plants, which in turn may attract foraging bears and other wildlife.…”
Section: Introductionmentioning
confidence: 97%